Green Banking and Financial Inclusion as Strategic Drivers of Financial Performance in The Indonesian Banking Sector - Ulfa, Rafidah; Isnurhadi, Isnurhadi; Yuliani, Yuliani (Economics, Business, Accounting & Society Review, 2025)
The growing global focus on sustainability has prompted the banking industry to integrate environmental and social considerations into its operational and financial strategies. In Indonesia, this transformation is closely tied to the implementation of green banking and the expansion of financial inclusion as dual drivers of sustainable development. This study aims to examine the influence of green banking practices and the degree of financial inclusion on the financial performance of banks in Indonesia. A quantitative research design was employed using secondary data derived from annual and sustainability reports of commercial banks between 2018 and 2023. Panel data regression analysis was conducted to test the relationship between variables, supported by diagnostic and model selection tests such as the Chow, Hausman, and Lagrange Multiplier tests. The results reveal that both green banking and financial inclusion have a positive and significant effect on bank profitability. Green banking enhances performance by promoting environmentally responsible financing, operational efficiency, and stakeholder trust, while financial inclusion—measured by branch network expansion—strengthens deposit mobilization and credit distribution, improving overall profitability. These findings confirm that sustainability and inclusivity are complementary strategies for achieving long-term financial success. The study contributes to the literature on sustainable finance by providing empirical evidence from a developing-country context and offering insights for policymakers and banking practitioners to harmonize profitability with environmental and social objectives.